1982
DOI: 10.1002/1097-0142(19821215)50:12<2740::aid-cncr2820501208>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Results of LSA2-L2 therapy in 26 children with non-hodgkin's lymphoma

Abstract: Twenty‐six children with non‐Hodgkin's lymphoma (NHL), 17 boys and nine girls, were treated with the LSA2‐L2 protocol. Seven children had Stage I or II, 16 Stage III and three Stage IV according to Murphy's staging system. Eight children had their primaries in peripheral lymph nodes, eight in the abdomen, six in the mediastinum and four in other sites. All tumors were classified histologically according to four different classifications. Overall disease‐free actuarial survival is 53.6%. Complete responders sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

1984
1984
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 17 publications
1
3
0
2
Order By: Relevance
“…Five days after diagnosis therapy was started using the LSA2-L2 protocol (6-Thioguanin and BCNU were not available at that time and had to be replaced by 6-mercaptopurine and cyclophosphamide) (1-3, 13,15). Already during the induction chemotherapy liverspleen scan follow-up studies showed a reduction of the liver size and a decrease of portal vein occlusion.…”
Section: Case Reporisupporting
confidence: 58%
“…Five days after diagnosis therapy was started using the LSA2-L2 protocol (6-Thioguanin and BCNU were not available at that time and had to be replaced by 6-mercaptopurine and cyclophosphamide) (1-3, 13,15). Already during the induction chemotherapy liverspleen scan follow-up studies showed a reduction of the liver size and a decrease of portal vein occlusion.…”
Section: Case Reporisupporting
confidence: 58%
“…The two year failure-free survival of the patient group with nonlocalized, nonlymphoblastic NHL (the majority of them having the primary site in the abdomen) was only 57% on the COMP and only 25 % on the LSA2-Lz regimen. These findings are supported by a smaller study performed by Pichler et a1 [30]. They have treated 26 children according to the LSA2-L2 protocol of Wollner.…”
Section: Onementioning
confidence: 53%
“…Cure rates are still poor for children with diffuse, undifferentiated histologies who present with widespread disease [94,95]. The application of leukemia-type treatments in these patients has been relatively unsuccessful.…”
Section: I11mentioning
confidence: 99%